Behaviors to Prevent Needle Stick Injury Among Nursing Students : A Systematic Literature Review - Saparwati, Mona; Trimawati; Achmad Syaifudin (Indonesian Journal of Nursing Research (IJNR), 2025)
The highest incidence of accidents and safety issues among nursing students during clinical practice is needle stick injury (NSI). Various efforts have been made to develop behaviors that prevent such incidents. This study is a literature review adapted from the Arskey and O'Malley framework. The Prisma-Scr flowchart was used to display the literature search flow. Articles for this study were searched using  five search engines: PubMed, Sage, Wiley, Scopus, and ScienceDirect. The keywords used for literature search were occupational injury OR accidental AND needlestick injury AND nursing student AND program. The inclusion criteria used were publication between 2013 and 2023, articles in English, and a focus on preventing needle stick injuries among nursing students. The review results showed that there were 25 potentially relevant articles, and 10 articles met the selection criteria. The articles were from several different countries, and 10 articles that met the criteria used quantitative and qualitative designs. This review revealed three themes, namely the incidence of needle stick injuries among nursing students, nursing students' understanding of preventing NSI, and efforts to prevent NSI. NSI incidents still occur among nursing students who conduct clinical practice in hospitals. Nursing students' understanding of preventing NSI is obtained through education from academic institutions and hospitals. Efforts to improve knowledge, attitudes, and behaviors to prevent NSI are carried out through education, training, the use of safe needles, and communication.